Peran Administrasi Kurikulum dalam Mengoptimalkan Pembelajaran - Alda Novita; Aida Gusmanita; Meri Rahma Yanti; Sulva Syafira Indah; Yessi Rifmasari (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The purpose of writing this scientific paper is to explain the importance of curriculum administration, the process or stages of curriculum administration and the active role of teachers in curriculum administration. If the curriculum administration is running as it should, then the learning objectives will be achieved. Based on a number of studies, management implementation is often hampered by limited resources, inappropriate policies and lack of active participation. This research uses a literature study method to examine this problem more deeply.